2019
DOI: 10.2337/db19-0271
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Both Central and Peripheral Neuropathy in Mouse Models of Type 1 and Type 2 Diabetes by the Neurogenic Molecule NSI-189

Abstract: While peripheral neuropathy is the most common complication of long-term diabetes, cognitive deficits associated with encephalopathy and myelopathy also occur. Diabetes is a risk factor for Alzheimer disease (AD) and increases the risk of progression from mild cognitive impairment to AD. The only current recommendation for preventing or slowing the progression of peripheral neuropathy is to maintain close glycemic control, while there is no recommendation for central nervous system disorders. NSI-189 is a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…b Corneal nerve density (SBNP) was measured by confocal microscopy in control or oxaliplatin-treated (CIPN) female Swiss Webster mice before (pre) and 2 weeks after (+MT7) daily delivery of MT7 to one eye (30 μl of 25 ng/ml solution), Monday-Friday, for 2 weeks. In this study, the SBNP was measured by tracing all nerves and recording total pixels/ image area [58]. Data are group mean + SEM of N = 7-9/group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…b Corneal nerve density (SBNP) was measured by confocal microscopy in control or oxaliplatin-treated (CIPN) female Swiss Webster mice before (pre) and 2 weeks after (+MT7) daily delivery of MT7 to one eye (30 μl of 25 ng/ml solution), Monday-Friday, for 2 weeks. In this study, the SBNP was measured by tracing all nerves and recording total pixels/ image area [58]. Data are group mean + SEM of N = 7-9/group.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal nerves of the sub-basal nerve plexus were imaged in anesthetized mice using a Heidelberg Retina Tomograph 3 with Rostock Cornea Module (Heidelberg Engineering, Heidelberg Germany) as described elsewhere [57]. Corneal nerve density was measured in 5 consecutive images (2-μm intervals) of the sub-basal nerve plexus (SBNP) between the corneal epithelium and stroma and quantified either as occupancy using an 8 × 8 grid layered onto each image [56] or as pixel density following tracing of all visible nerves using ImageJ software [58].…”
Section: Corneal Confocal Microscopymentioning
confidence: 99%
“…We recently reported that NSI-189 prevented and reversed memory impairments, restored hippocampal neurogenesis, and enhanced expression of synaptic markers in the CNS of type 1 or type 2 diabetic mice while concurrently ameliorating peripheral neuropathy [16]. Intriguingly, NSI-189 applied to sensory neurons in vitro both enhanced neurite outgrowth and stimulated maximal and spare respiratory capacity [16]. The present study expands investigation of the ability of NSI-189 to stimulate mitochondria and ameliorate indices of CNS and PNS dysfunction in the Zucker diabetic fatty (ZDF) rat model of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials in subject with major depressive disorder (MDD) demonstrated that NSI-189 is safe and had long-lasting antidepressive and procognitive effects [14,15]. We recently reported that NSI-189 prevented and reversed memory impairments, restored hippocampal neurogenesis, and enhanced expression of synaptic markers in the CNS of type 1 or type 2 diabetic mice while concurrently ameliorating peripheral neuropathy [16]. Intriguingly, NSI-189 applied to sensory neurons in vitro both enhanced neurite outgrowth and stimulated maximal and spare respiratory capacity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, DPN improvement was evaluated by MNCV and sensory sensitivity assays in the current work, although these assays are very potent for DPN study (28,49) according to the Diabetes Complications Consortium guidelines, sensory nerve conduction velocity (SNVC)-related assays should be of high complementation to our work.…”
Section: Discussionmentioning
confidence: 99%